Implementasi Kegiatan Usap Abur dalam Meningkatkan Perkembangan Motorik Halus Anak Kelompok A di RA Nurul Ilmi 1 - Asiah, Asiah; Salhah, Salhah; Khalisa, Khalisa (Institut Agama Islam Ngawi, 2026)
Fine motor development is one of the areas that must be stimulated to support other developmental areas. RA Nurul Ilmi 1 Daha Utara is one of the early childhood education institutions that implements learning activities to develop children's fine motor skills through rubbing, as this medium is considered capable of stimulating children's motor development. The purpose of this study is to find out how the implementation of rubbing activities to improve children's fine motor development in group A to find out the supporting and inhibiting factors in the implementation of rubbing activities in improving children's fine motor development in group A RA Nurul Ilmi 1 Daha Utara District Hulu Sungai Selatan Regency. This research is a field study with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The interview technique used was a structured interview guide. The results of this study indicate that fine motor development through the rubbing activity at RA Nurul Ilmi 1 has experienced significant progress. The implementation of the rubbing activity in Group A of RA Nurul Ilmi 1 was carried out systematically through three main stages: 1) implementation planning, namely preparing the RPPH, media and tools used. 2) implementation, namely initial activities, core activities, and closing activities. 3) evaluation, in the form of child development assessment notes in the form of checklists, anecdotal notes, and work results. Factors that influence children’s fine motor development through the rub-abur activity are: family factors, educator factors, and the child's own creativity factors.